2021
DOI: 10.1002/cpp.2697
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of the other in the self as a potential risk factor for prolonged grief disorder: A comparison of patients with matched bereaved healthy controls

Abstract: Pathological grief has received increasing attention in recent years, as about 10% of the bereaved suffer from one kind of it. Pathological grief in the form of prolonged grief disorder (PGD) is a relatively new diagnostic category which will be included into the upcoming ICD-11. To date, various risk and protective factors, as well as treatment options for pathological grief, have been proposed. Nevertheless, empirical evidence in that area is still scarce. Our aim was to identify the association of interpers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Combined with the results obtained from the IIP-D, it could be argued that the cooperation behavior in the FIPD is the result of warm-submissive behavior and the underlying will to please others, however, interpreting the group × repeated measures interaction, which demonstrated that the number of shared tokens tended to be distributed differently across the 30 trials for the two groups, could also indicate a lack of social flexibility (Nelson & Guyer 2011) due to deficient valuation, inhibition, or rule use. Without further evidence, we suggest that valuation may be most deficient in PGD, leading to stronger commitment, higher dependency, and a higher than normal tendency to feel fused with the bereaved, as shown by other studies (Harrison et al 2021). Hence, in persistently over-valuating the other, they might lack the capability to adapt to changes in the relationship.…”
Section: Interpretations and Conclusionmentioning
confidence: 55%
See 2 more Smart Citations
“…Combined with the results obtained from the IIP-D, it could be argued that the cooperation behavior in the FIPD is the result of warm-submissive behavior and the underlying will to please others, however, interpreting the group × repeated measures interaction, which demonstrated that the number of shared tokens tended to be distributed differently across the 30 trials for the two groups, could also indicate a lack of social flexibility (Nelson & Guyer 2011) due to deficient valuation, inhibition, or rule use. Without further evidence, we suggest that valuation may be most deficient in PGD, leading to stronger commitment, higher dependency, and a higher than normal tendency to feel fused with the bereaved, as shown by other studies (Harrison et al 2021). Hence, in persistently over-valuating the other, they might lack the capability to adapt to changes in the relationship.…”
Section: Interpretations and Conclusionmentioning
confidence: 55%
“…However, studies have shown that PGD is associated with insecure attachment and that PGD patients often have formed a very close, almost dependent relationship with the deceased, which makes it difficult for them to form new relationships (Burke & Neimeyer 2013;Maccallum & Bryant 2018;Mancini et al 2015). In fact, PGD patients have been found to feel significantly closer to the deceased than to their closest living friend, and to experience higher than normal identity fusion with the deceased (Harrison et al 2021). Such higher self-other fusion is associated with more empathy and altruism (Cialdini et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, recent studies found that perceived interpersonal closeness to the deceased was an important risk factor across bereaved spouses and adult children, and both subgroups show similar patterns of decreasing symptoms over time (C. B. Harris et al, 2023;Harrison et al, 2022). Thus, perceived interpersonal closeness and merged identity with the deceased may increase the risk of developing PGD rather than the factual relationship to the deceased.…”
Section: Temporal Associations Between Complicated Grief Reactionsmentioning
confidence: 87%
“…On the other hand, psychoanalytic theory suggests that a conflicted relationship before death is also linked to loss-related psychopathology, presumably because it complicates resolving attachment issues with the deceased and completing the decathexis (i.e., emotional withdrawal of one's attachment to the deceased; Freud, 1917;Parkes, 1991;Worden, 2015). Empirical studies confirmed that predeath closeness to and conflict with the deceased was positively associated with postdeath pathological grief, depressive symptoms, and psychological distress (Coelho et al, 2022;Harrison et al, 2022;Keser et al, 2022;Lee et al, 2022;Sekowski & Prigerson, 2022;Smigelsky et al, 2020;Tang et al, 2021). When taking closeness and conflict into consideration simultaneously, however, the two dimensions seem to contribute differently to psychopathological symptoms.…”
Section: Quality Of Relationship As a Risk Factormentioning
confidence: 99%